2018
DOI: 10.5851/kosfa.2018.e33
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of an Anti-listerial Bacteriocin from Leuconostoc lactis SD501

Abstract: Although bacteriocins with anti-listerial activity have been isolated from a wide variety of lactic acid bacteria, little is known about those from Leuconostoc lactis, a heterofermentative bacterium that produces diacetyl and exopolysaccharides in dairy foods. In this study, an anti-listerial bacteriocin was isolated from Leuc. lactis SD501 and characterized. It was particularly potent against Listeria monocytogenes and also inhibited Enterococcus faecalis. Anti-listerial activity reached a maximum during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“… 188 Several studies have identified bacteriocin‐producing strains of leuconostocs (Table 6 ). 189 , 190 , 191 Most Leuconostoc bacteriocins are classified as Class II, which are small (less than 10) and heat stable. They are non‐lanthionine‐containing bacteriocins without post‐translational modification.…”
Section: Classification Of Bacteriocinsmentioning
confidence: 99%
“… 188 Several studies have identified bacteriocin‐producing strains of leuconostocs (Table 6 ). 189 , 190 , 191 Most Leuconostoc bacteriocins are classified as Class II, which are small (less than 10) and heat stable. They are non‐lanthionine‐containing bacteriocins without post‐translational modification.…”
Section: Classification Of Bacteriocinsmentioning
confidence: 99%
“…Studies have shown that the sensory characteristic properties of goat yogurt can be greatly improved by integrating the cultures of Leuconostoc lactis with traditional yogurt starters [11]. Moreover, Leuconostoc lactis is one of the most important species in the genus Leuconostoc, which plays an important role in the production of glucan and bacteriocin in the food industry [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…citreum HW02 (Zangeneh et al ., 2020). Similar results showing the production of bacteriocin at the early exponential phase have been reported (Xiraphi et al ., 2008; Hwang et al ., 2018; Woo et al ., 2021). Maximal production of bacteriocin HW02 was detected at the middle of the stationary phase (at 12 h) as 320 AU mL −1 , and the pH was 4.51.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the location of the inhibition zone, the crude bacteriocin molecular weight was determined to be approximately 7.4 kDa, which is similar to the finding reported in a study by Hwang et al . (2018). However, the determination of molecular weight using the crude bacteriocin cannot reveal the accurate molecular weight because a protein having a molecular weight similar to that of bacteriocin can be precipitated along with bacteriocin HW02 in the ammonium sulphate precipitation step.…”
Section: Resultsmentioning
confidence: 99%